Postcolonial realms of memory : sites and symbols in modern France - Achille, Etienne; Forsdick, Charles; Moudileno, Lydie (Contemporary French and francophone cultures, 2020)
Addressing the remarkable absence of colonial legacy from Pierre Nora's Les Lieux de mémoire, the present volume fosters a new reading of the French past by discerning and exploring an initial repertoire of realms that bridges the gap between traditionally instituted French memory and traces of the colonial on the Republic's soil, including its Outremer.